Physical characteristics of eddible film from carrageenan with liquid smoke addition - Moga, Tomy; Montotolalu, Roike I; Berhimpon, Sigfried; Mentang, Feny (Universitas Sam Ratulangi, 2018)
Title (Bahasa Indonesia): Karakteristik fisik edible filmdarikaraginan dengan penambahan asap cair Packaging materials food which are multifunctional and safe for consumers and the environment is thefocus of today’sfood packaging studies. Edible films that are made from carrageenan is one form of primary packaging for food. The physical properties of the packaging has become an important component to be consideredin choosing packaging. Thestudywasconducted to determine the effect of carrageenan concentration on the physical properties of solubility, thickness, tensile strength, percentage of elongation and water vapor transmission rate. The result showed that edible film processed fromcarrageenan with different concentrations have different physical properties. The higher the concentration of carrageenan used in the manufacture of edible film, the stronger the solubilityof the edible film, the stronger the attractiveness, andthe thicker and more resistant. Vapor transmission rateis getting lower, or in other word the ability to withstand wateris high.Kemasan bahan pangan yang multifungsi dan aman bagi konsumen dan lingkungan menjadi fokus kajian kemasan bahan pangan saat ini. Edible filmdari bahan karaginan merupakan salah satu bentuk kemasan primer bagi bahan pangan. Sifat fisik kemasan menjadi komponen penting yang dipertimbangkan dalam memilih kemasan. Penelitian inidilakukan untuk mengetahui pengaruh konsentrasi karaginan terhadap sifat fisik kelarutan, ketebalan, kuat tarik, persentasi perpanjangan putus dan laju transmisi uap air. Hasilnya diperolehedible filmyang diproses dari karaginan dengan konsentrasi yang berbeda memiliki sifat fisik yang berbeda. Semakin tinggi konsentrasi karaginan yang digunakan di dalam pembuatan edible film, maka edible filmyang dihasilkan semakin tinggi kelarutannya, semakin kuat daya tariknya, semakin tebal dan semakin tahan serta laju transmisi uapnya makin rendah atau kemampuan menahan airnya tinggi.